A MECHANISM OF FORMATION OF RADICALS IN CRYSTAL KDP (KH2PO4) - Кoketai, Т.; Тagayeva, B.; Тussupbekova, А.; Mussenova, E. (KarU, 2015)
The mechanisms of formation of A-radicals in the crystal K2SO4. Calculations established that the excitation of oscillations on the O-H bond in the triplet excitons in the excited state leads to a situation vibronic instability leading to the disintegration of the exciton with the formation of hydrogen atoms and A- radical.
Keywords: Crystal; potassium dihydrogen phosphate (KDP); exciton